The Position of the Fatwa of the Indonesian Ulema Council Number 33 of 2018 Concerning the Measles-Rubella Vaccine: National Law Perspective - Muammar Arafat Yusmad; Dirah Nurmila Siliwadi (Jurnal Ilmiah Al-Syir'ah, 2022)
This study aims to analyze the position and validity of the fatwa of the Indonesian Ulema Council (MUI) Number 33 of 2018 from the perspective of national law. And analyze the position of the fatwa of the Indonesian Ulema Council Number 33 of 2018 in terms of sociological, philosophical, and juridical application aspects. This research is library research sourced from secondary data with a statutory approach, namely an approach with an analysis of national legal rules and regulations related to Islamic law. The results show that the Fatwa of the Indonesian Ulema Council is not binding to be obeyed and is only in the form of appeals and suggestions given to Muslims because the Fatwa of the Indonesian Ulema Council is not included in the national legal framework in Indonesia. The fatwa regarding the Measles-Rubella (MR) vaccine is allowed (permissible) on the grounds of a star’s emergency. Yes, with the applicable provisions. The 2018 Fatwa Number 33 by the Indonesian Ulema Council applies sociologically because the Muslim community accepts the fatwa and makes a warning about the status of the Measles-Rubella vaccine.